Foodcourt Online Usakti Campus A - Fikri Ismaya; Syaifudin Abdullah; Syandra Sari (Penerbitan Universitas Trisakti, 2021)
The era is progressing from year to year. The number of food businesses that are integrated with the internet to market food products online, payments do not use cash and food deliveries do not need to be recorded because the recording has been done automatically by the application. The canteens in the Usakti Campus A area have not been registered on the online application so food orders are still manual, payments must be made in cash, and food shipments are still recorded manually. In order for the sales of these canteens to be carried out online, an online application needs to be developed so that prospective buyers can view food products online, order food online, make payments in cash, and send food items recorded automatically by the application. This online application development is carried out using the waterfall software development method which is based on the System Development Life Cycle (SDLC), and uses the Unified Modeling Language (UML) to create application processes with Use Cases, Activity Diagrams, Sequence Diagran, and Class Diagrams. Based on the evaluation carried out on application users, it can be concluded that the Usakti food court application developed can make it easier for buyers to order food from their payments. With this application, buyers do not need to come physically to the canteen to buy food. As for sellers, using this application can expand their market reach and can create promo coupons, view food orders via the internet and using Unified Modeling Language (UML) to create application processes with Use Cases, Activity Diagrams, Sequence Diagran, along with Class Diagrams. Based on the evaluation carried out on application users, it can be concluded that the Usakti food court application developed can make it easier for buyers to order food from their payments. With this application, buyers do not need to come physically to the canteen to buy food. As for sellers, using this application can expand their market reach and can create promo coupons, view food orders via the internet and using Unified Modeling Language (UML) to create application processes with Use Cases, Activity Diagrams, Sequence Diagran, along with Class Diagrams. Based on the evaluation carried out on application users, it can be concluded that the Usakti food court application developed can make it easier for buyers to order food from their payments. With this application, buyers do not need to come physically to the canteen to buy food. As for sellers, using this application can expand their market reach and can create promo coupons, view food orders via the internet Based on the evaluation carried out on application users, it can be concluded that the Usakti food court application developed can make it easier for buyers to order food from their payments. With this application, buyers do not need to come physically to the canteen to buy food. As for sellers, using this application can expand their market reach and can create promo coupons, view food orders via the internet Based on the evaluation carried out on application users, it can be concluded that the Usakti food court application developed can make it easier for buyers to order food from their payments. With this application, buyers do not need to come physically to the canteen to buy food. As for sellers, using this application can expand their market reach and can create promo coupons, view food orders via the internet